Paradisal love : Johann Gottfried Herder and the Song of Songs - Baildam, John D. (Journal for the study of the Old Testament. Supplement series, 1999)
This is the first comprehensive study of Herder's preoccupation with the Song of Songs, Baildam considers the importance of this poetry in his thinking, and examines his commentaries and translations of 1776 and 1778. Despite Herder's claims to the contrary, his own cultural position is revealed in his translations, and in his unique interpretation of the work as the voice of pure, paradisal love. Starting with Herder's interest in the Song of Songs between 1765 and 1778, this book sets his reflections in the wider context of his relativistic views on the nature of poetry, contemporary German.